Tis21 Expression Marks Not Only Populations of Neurogenic Precursor Cells but Also New Postmitotic Neurons in Adult Hippocampal Neurogenesis - Attardo, Alessio (Oxford University Press, 2010)
During embryonic cortical development, expression of Tis21 is associated with cell cycle lengthening and neurogenic divisions of progenitor cells. We here investigated if the expression pattern of Tis21 also correlates with the generation of new neurons in the adult hippocampus. We used Tis21 knock-in mice expressing green fluorescent protein (GFP) and studied Tis21-GFP expression together with markers of adult hippocampal neurogenesis in newly generated cells. We found that Tis21-GFP 1) was absent from the radial glia–like putative stem cells (type-1 cells), 2) first appeared in transient amplifying progenitor cells (type-2 and 3 cells), 3) did not colocalize with markers of early postmitotic maturation stage, 4) was expressed again in maturing neurons, and 5) finally decreased in mature granule cells. Our data show that, in the course of adult neurogenesis, Tis21 is expressed in a phase additional to the one of the embryonic neurogenesis. This additional phase of expression might be associated with a new and different function of Tis21 than during embryonic brain development, where no Tis21 is expressed in mature neurons. We hypothesize that this function is related to the final functional integration of the newborn neurons. Tis21 can thus serve as new marker for key stages of adult neurogenesis.